AB0736 SEVERITY OF NAIL PSORIASIS SCORE (SNAPS) IS SENSITIVE TO CHANGE IN A COHORT OF PATIENTS WITH PSORIATIC ARTHRITIS TREATED WITH ETANERCEPT. (13th June 2020) - Antony, A.; Saeed, S.; Hart, D.; Nair, P.; Cavill, C.; Korendowych, E.; Mchugh, N.; Lovell, C.; Tillett, W.
Abstract : Background: The Severity of Nail Psoriasis Score (SNAPS; range 0-40: scored one point each for the presence of pitting, onycholysis, hyperkeratosis and/or severe nail disease # in each fingernail) has been utilised to collect data regarding psoriatic nail dystrophy in the Bath Psoriatic Arthritis (PsA) Longitudinal cohort for many years. SNAPS has construct validity in PsA with the modified Nail Psoriasis Severity Index (mNAPSI) as a comparator instrument and appears to be more feasible than mNAPSI with excellent reliability 1 . Objectives: We aimed to determine if SNAPS could demonstrate longitudinal sensitivity to change in a cohort of patients treated with biological disease modifying anti-rheumatic drugs (bDMARDs) and therefore be utilized prospectively in observational and clinical trial settings. Methods: Patients enrolled in the Bath PsA longitudinal cohort routinely undergo clinical assessments including a 66/68 Swollen and Tender Joint Count (SJC/TJC), Psoriasis Area Severity Index (PASI), Patient Global Assessment (PtGA) and Physician Global Assessment (PhGA), as well as complete patient-reported outcome measures such as the Health Assessment Questionnaire (HAQ) and Dermatology Quality of Life (Derm-QoL). All patients who commenced treatment with Etanercept and had available outcome data at baseline, 3 months and 6 months were included in this retrospective analysis. Baseline demographics were recorded and paired t-tests were utilized to assess the change in SNAPS at 3 and 6 months. The effect size and measurement error of SNAPS in this cohort were measured. Correlations between SNAPS and other outcome measures were assessed using Pearson's r. Results: Fifty-seven patients (32 male and 25 female) with available data were retrospectively analysed. The mean (±SD) age of the cohort and duration of disease was 61.3 (±11.55) and 13.3 (±10.82) years respectively. The mean SNAPS at baseline was 3.7 (±6.13) and improved to 2.0 (3.74, p=0.018) at 3 months and 1.2 (2.40) at 6 months (p=0.001 for change from baseline and p=0.039 for change from month 3). The smallest detectable difference at 3 months for SNAPS in this cohort was 1.35, representing 3.37% of the range of the score (Table 2). The standardised response mean (SRM) was 0.32 at 3 months and 0.44 at 6 months. There was a modest correlation between the improvement in the SNAPS score and the improvement in PASI and Derm QOL at 3 months (r = 0.511 and 0.558 respectively, p=0.001) and 6 months (r= 0.672, p<0.001 and r=0.510, p=0.003 respectively). Conclusion: SNAPS demonstrates sensitivity to change in response to treatment with a bDMARD and could be a potential outcome measure for the assessment of treatment efficacy in prospective studies. References: [1]Antony A, Hart D, Cavill C, Korendowych E, McHugh N, Lovell C, Tillett W. The 'Severity of Nail Psoriasis Score' (SNAPS) Is Feasible, Reliable and Demonstrates Construct Validity Against the mNAPSI in an Observational Cohort of Patients with Psoriatic Arthritis [abstract]. Arthritis Rheumatol. 2019; 71 (suppl 10). Disclosure of Interests: Anna Antony: None declared, Sadaf Saeed: None declared, Darren Hart: None declared, Preeti Nair: None declared, Charlotte Cavill: None declared, Eleanor Korendowych: None declared, Neil McHugh: None declared, Christopher Lovell: None declared, William Tillett Grant/research support from: AbbVie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant of: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, MSD, Pfizer Inc, UCB, Speakers bureau: AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, Pfizer Inc, UCB